Upaya Menumbuhkan Karakter Nasionalisme Siswa Melalui Metode Role Playing Kelas IX B Di SMP Budi Utomo Prambon Sidoarjo - Ma'rufah, Siti (Jurnal Dialektika Pendidikan IPS, 2023)
This reserch departs from the reduced character values of students at SMP Budi Utomo Prambon Sidoarjo. Where students have been carried away by external currents, as can be seen from the lack of appreciation when carrying out the flag ceremony process. Such a situation of students can occur due to environmental factors and family. By looking at the reality at the school, the researcher is interested in conducting research using the Role Playing learning method. With this research, it is expected that students can improve their nationalism character. This study uses the Character Theory initiated by Thomas Lickona. The location of this research is Budi Utomo Prambon Middle School Sidoarjo. The data that has been obtained is the result of observation, interview and documentation. The approach to this research is a qualitative approach with a case study design. The data analysis technique in this study is in accordance with the Miles and Hubberman model which includes data reduction, data presentation and data conclusions. The results of this study indicate that students at Budi Utomo Prambon Sidoarjo Middle School include the following (1) Planning includes preparation of lesson plans, (2) Implementation includes opening learning activities, core learning activities (learning methods, learning media, learning resources and learning assessment), (3) Evaluation includes assessing students attitudes (honesty, discipline, tolerance and mutual cooperation). Through learning planning it is done by writing down the nationalism character values into the RPP on KI 2, the learning objectives and the content of the nationalism character contained in the learning activities; through the implementation of learning the character of nationalism is built using the role playing/drama method, with learning media that supports the drama activities, learning resources in the form of the social studies student books and drama scripts, then assessments or assessment use summative and formative assessments, as well as through evaluation of attitudes, knowledge and skills.